Assessment of the Logistic System of Fuel Life Cycle Using the LCA Method (Agricultural Engineering, 2016)
This paper presents the logistic system of fuel life cycle, covering diesel oil and the mixture of rapeseed oil and butanol (2:3 ratio), using the Life-Cycle Assessment (LCA) method. This method is a technique in the field of management processes with a view to assessing the potential environmental hazards. Our intention was to compare the energy consumption needed to produce each of the test fuels and emissions of selected substances generated during the production process. The study involved 10,000 liters of diesel and the same amount of rapeseed oil and butanol mixture (2:3 ratio). On the basis of measurements the following results were obtained. To produce a functional unit of diesel oil (i.e. 10,000 liters) it is necessary to extract 58.8 m3 of crude oil. The entire life cycle covering the consumption of 10,000 liters of diesel consumes 475.668 GJ of energy and causes the emission to air of the following substances: 235.376 kg of COx, 944.921 kg of NOx, 83.287 kg of SOx. In the ease of a functional unit, to produce a mixture of rapeseed oil and butanol (2:3 ratio) 10,000 kg of rapeseed and 20,350 kg of straw should be used. The entire life cycle of 10,000 liters of a mixture of rapeseed oil and butyl alcohol (2:3 ratio) absorbs 370.616 GJ of energy, while emitting the following air pollutants: 105.14832 kg of COx, 920.03124 kg of NOx, 0.162 kg of SOx. Analysis of the results leads to the conclusion that it is oil refining which is the most energy-intensive and polluting process in the life cycle of diesel. The process consumes 41.4 GJ of energy, and causes a significant emission of sulfur oxides (50 kg). In the production of fuel that is a mixture of rapeseed oil and butyl alcohol (2:3 ratio), rape production is the most energy-intensive manufacturing process is (absorbs 53.856 GJ of energy). This is due to the long operation time of the farm tractor and combine harvester. The operation of these machines leads also to the emission of a significant amount of pollution in the form of COx (2.664 kg) and NOx (23.31 kg).